The Influence Of Promotion And Customer Behavior On The Decision To Pursue Postgraduate Studies Mediated By Trust - Cahaya, Yohanes Ferry; Siswanti, Indra; Syamsunasir, Syamsunasir (Management Research Studies Journal, 2025)
This study examines the influence of promotion and customer behavior on the decision to continue studying for a Master's degree with trust as a mediating variable. Using a quantitative approach with PLS-SEM analysis, the study found that customer behavior has a significant direct influence on the decision to continue studying (β=0.661, p<0.001), while promotion and customer behavior have a significant effect on the formation of trust. However, trust was not proven to mediate the relationship between the independent variables and the decision to continue studying, creating a "trust-action gap" phenomenon. The implication is that higher education institutions need to integrate customer experience management with promotional strategies that build trust, as well as develop mechanisms for converting trust into actual decisions.